RADI-13. IMPACT OF CITV AND BRAF MUTATION ON MELANOMA METASTASIS RESPONSE TO STEREOTACTIC RADIOSURGERY. (12th August 2019) - Alattar, Ali; Joshi, Rushikesh; HIrshman, Brian; Carroll, Kate; Nagano, Osamu; Aiyama, Hitoshi; Serizawa, Toru; Yamamoto, Masaaki; Chen, Clark
Abstract: INTRODUCTION: Survival prognostication is an important aspect of personalizing oncologic care for patients with melanoma brain metastasis (BM). We previous demonstrated the utility of a cumulative intracranial tumor volume modified diagnosis-specific graded prognostic assessment scale (CITV-dsGPA) for SRS-treated melanoma BM patients. Pertinent prognostic variables in this model included age, Karnofsky performance status (KPS), and CITV. Here we determined whether the incorporation of BRAF mutation status into this CITV-modified scale further enhanced its prognostic accuracy. METHODS: We collated the survival pattern of 331 melanoma BM patients with known BRAF mutation status treated with stereotactic radiosurgery (SRS) and validated our findings in an independent cohort of 174 patients. All patients with BRAF mutation were treated with BRAF inhibitors. The prognostic utility of the model with and without BRAF mutation information was compared using the net reclassification index (NRI > 0) and integrated discrimination improvement (IDI) metric. RESULTS: Presence of the BRAF mutation was associated with a reduced hazard of death in univariate Cox proportional hazards survival analysis (hazard ratio (HR) 0.74, p< 0.001). This effect persisted in a multivariate model that controlled for age, KPS, and CITV (HR 0.72, p< 0.001). Addition of BRAF mutation status to the CITV-ds-GPA model for melanoma significantly improved its prognostic value, with NRI >0 of 0.294 (p=0.01) and IDI of 0.017 (p=0.02). We validated these findings in an independent cohort of 174 melanoma patients. CONCLUSIONS: Optimal survival prognostication for SRS-treated patients with melanoma BM requires an integrated assessment of age, KPS, CITV, and BRAF mutation status.